Mahnen und Regieren : Die Metapher des Hirten im früheren Mittelalter - Suchan, Monika (2015)
The shepherd metaphor is widely diffused in many civilizations. Using this metaphor Pope Gregory introduced a successful leadership model which, as the Author shows, was further developed by the clergy and the kings in Carolingian times. This book sheds new light on politics in the Early Middle Ages, depicting it less as a form of power legitimated by divine right, than as social discourse between leadership groups.